Exploring the Role of Infographics for Summarizing Medical Literature - Martin, Lynsey J.; Turnquist, Alison; Groot, Brianna; Huang, Simon Y.M.; Kok, Ellen; Thoma, Brent; van Merriënboer, Jeroen J.G. (Health professions education, 2019)
To investigate differences in (1) reader preference, (2) cognitive load during summary review, and (3) delayed information retention between infographic article summaries and traditional text-only research abstracts. The three study outcomes were assessed using a two-phase within-subjects experiment. In phase 1, participants rated cognitive load as the mental effort they invested in reviewing eight article summaries (four in infographic format and four in text-only abstract format) on the 9-point Paas scale (1=low mental effort, 9=high mental effort) and indicated their preferred summary format on a 9-point preference scale (1=preferred infographics, 9=preferred text-only abstracts). Four weeks later, phase-2 tested delayed information retention via two free-recall and two cued-recall questions per article. Participants preferred infographic summaries to traditional text-only research abstract summaries as evidenced by a mean format preference score (mean±standard deviation) of 3.97±2.48 (t(71)=13.6, p=0.01) which was significantly more positive than the neutral score of 5 on the 9 point preference scale. Mean mental effort during summary review was lower for infographics (4.30±1.34) than for text-only abstracts (5.06±1.35, t(70)=4.41, p=0.01). There was no statistically significant difference in delayed information retention. This study suggests that infographics could play a role in summarizing medical research literature. While no difference was found in delayed information retention, infographics were associated with higher reader preference and lower cognitive load during summary review. Further research should clarify the practical implications of these findings. [Display omitted]